Force, content and the varieties of subject - Schmitz, Michael (Language & communication, 2019)
This paper argues that to account for group speech acts, we should adopt a representationalist account of mode / force. Individual and collective subjects do not only represent what they e.g. assert or order. By asserting or ordering they also indicate their theoretical or practical positions towards what they assert or order. The ‘Frege point’ cannot establish the received dichotomy of force and propositional content. On the contrary, only the representationalist account allows a satisfactory response to it. It also allows us to give a more satisfactory analysis of the speech act of inviting a joint commitment and to answer two important questions Bernhard Schmid has raised about group speech acts, namely whether there are 1st person plural forms of Moore’s paradox and of 1st person authority.